PEMASARAN PRODUK PERTANIAN : MASALAH DAN SOLUSINYA - Nikolas Fajar Wuryaningrat (Tasharruf: Journal Economics and Business of Islam, 2017)
AbstractAgriculture is an integral part of human life in this world. But agriculture, especially in Indonesia is still a small contributor to Indonesia's gross domestic income. This article is a literature review and review of information from various media in view of the overall agricultural marketing issues. The problems of marketing agricultural products grouped in the 4P marketing mix, and Agribusiness MIS problem are the solution offered in this article. Keyword : Marketing Mix, Agribusiness, MIS